Diskursus Manajemen Surat Masuk dan Implikasinya Terhadap Pengambilan Keputusan Organisasi - Safitri, Rini Rahma; Gita Asyari; Siregar, Muhammad Wafi; Tengku Darmansah (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
This study examines the discourse of incoming mail management and its implications for organizational decision-making. The background of this research stems from the phenomenon of inefficiency in managing incoming correspondence across various organizations, which potentially hinders strategic decision-making processes. The objectives are to analyze patterns of mail management, identify its impact on decision effectiveness, and provide systemic improvement recommendations. Using a qualitative method with thematic analysis approach, the study conducted in-depth interviews with 25 key informants and analyzed documents from 10 sample organizations. The findings reveal four critical issues: (1) fragmented distribution processes, (2) multi-layered approval hierarchies, (3) digital-physical system disparities, and (4) informal priority-setting practices. These findings demonstrate that incoming mail management affects not only administrative efficiency but also the quality, speed, and accountability of organizational decisions. Keywords: incoming mail, decision-making, organization